Sensory Augmentation for the Blind - Kärcher, Silke M.; Fenzlaff, Sandra; Hartmann, Daniela; Nagel, Saskia K.; König, Peter (Frontiers in Human Neuroscience, 2012)
Enacted theories of consciousness conjecture that perception and cognition arise from an active experience of the regular relations that are tying together the sensory stimulation of different modalities and associated motor actions. Previous experiments investigated this concept by employing the technique of sensory substitution. Building on these studies, here we test a set of hypotheses derived from this framework and investigate the utility of sensory augmentation in handicapped people. We provide a late blind subject with a new set of sensorimotor laws: A vibro-tactile belt continually signals the direction of magnetic north. The subject completed a set of behavioral tests before and after an extended training period. The tests were complemented by questionnaires and interviews. This newly supplied information improved performance on different time scales. In a pointing task we demonstrate an instant improvement of performance based on the signal provided by the device. Furthermore, the signal was helpful in relevant daily tasks, often complicated for the blind, such as keeping a direction over longer distances or taking shortcuts in familiar environments. A homing task with an additional attentional load demonstrated a significant improvement after training. The subject found the directional information highly expedient for the adjustment of his inner maps of familiar environments and describes an increase in his feeling of security when exploring unfamiliar environments with the belt. The results give evidence for a firm integration of the newly supplied signals into the behavior of this late blind subject with better navigational performance and more courageous behavior in unfamiliar environments. Most importantly, the complementary information provided by the belt lead to a positive emotional impact with enhanced feeling of security. This experimental approach demonstrates the potential of sensory augmentation devices for the help of handicapped people.